Retroperitoneal paraganglioma: A case report with review of literature - Bhagyashri R Hungund; Vishwanath M Pattanshetti; Ganga S Pilli; Ranjit Kangle; Ramesh Y Chavan (Wolters Kluwer Medknow Publications, 2018)
Retroperitoneal paragangliomas are rare neoplasms usually seen as histological surprises and can be confused with more common retroperitoneal neoplasms. The present case is reported to discuss the clinical presentation, radiological features, and histological features of a nonfunctioning retroperitoneal paraganglioma of unusual histology which presented as a diagnostic dilemma which was confirmed by immunohistochemistry.